Vibration suppression effect of porous graphene platelet coating on fiber reinforced polymer composite plate with viscoelastic damping boundary conditions resting on viscoelastic foundation. (15th June 2021) - Li, Hui; Gao, Zhijiang; Zhao, Jing; Ma, Hui; Han, Qingkai; Liu, Jinguo
Highlights: A new vibration suppression structure with mass-spring-damper system is proposed. The rule of mixture with complex modulus principle is implemented to describe the damping parameters of porous graphene. The sensitivity parameters of various damping designs for vibration suppression are discussed via parameter analysis. Abstract: This work is devoted to the investigation of vibration suppression effects of the viscoelastic foundation, viscoelastic damping boundary condition and porous graphene platelet coating (PGPC) on the fiber reinforced polymer (FRP) composite plate. A dynamic model is built by combining the first-order shear deformation theory, the multi-segment partition technique, the virtual spring technology, the Rayleigh-Ritz approach, and the mode strain energy method. Afterwards, the structural natural frequencies, modal shapes and modal damping ratios are calculated, as well as the verification of the convergence and the correctness of the constructed model. Finally, the vibration suppression effect of the FRP-PGPC composite plate with different parameters, such as geometrical and material parameters, foundation and boundary condition types, are discussed in details.